2016
DOI: 10.1016/j.ijscr.2016.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive angiomyxoma presenting with back and perineal bulge; a complex surgical approach: A case report

Abstract: Highlights90% of patients are women.Different incisions allows full mobilization of the tumor.Wide excision should keep capsule intact.R0 resection should be achieved.Follow-up should be at 1–2 yearly intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Distant metastatic disease, however, is rare. There are only two cases described in the literature with pulmonary metastases and six mediastinal lymph nodes [7][8][9][10]. In the present case, no metastatic disease was detected in the extension study, but in the pathological study, involvement of the deeper surgical margin of the lesion was observed, although this condition does not seem to affect the risk of recurrence, which is high per se [11].…”
Section: Discussionmentioning
confidence: 42%
“…Distant metastatic disease, however, is rare. There are only two cases described in the literature with pulmonary metastases and six mediastinal lymph nodes [7][8][9][10]. In the present case, no metastatic disease was detected in the extension study, but in the pathological study, involvement of the deeper surgical margin of the lesion was observed, although this condition does not seem to affect the risk of recurrence, which is high per se [11].…”
Section: Discussionmentioning
confidence: 42%
“…As emerged from our experience, and confirmed in the literature, the aspect of an aggressive angiomyxoma is often like a benign neoformation, such as lipomas or cysts, with a sort of soft, compact texture [ 2 , 4 , 5 , 6 ] and lobulated or spherical form, with an undefined capsule. The aggressivity of this type of tumor is usually limited to the nearest tissues, but some rare cases of pulmonary and lymph nodal metastasis have been reported [ 24 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The uniqueness of our work is not only for the analysis of the pathological management, but also for the presence of a complex, ongoing twin pregnancy and the observed sequelae of the treatment. To our knowledge, this is the most updated review on the topic [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The variety of the possible body locations, the association with pregnancy, and the few cases known in the literature make it difficult to formulate unique guidelines on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] The longest recurrence time reported in the literature is 20 years. [ 16 ] There are even reports of lung metastasis [ 17 , 18 ] and death [ 19 ] in patients. Therefore, patients need long-term follow-up after operation.…”
Section: Discussionmentioning
confidence: 99%